Slewing Bearing Design of Articulated Bogie for Urban Rail Vehicles - WANG Gaofeng; WANG Yanping; LI Guanghui; ZHANG Yaping; ZHANG Shaolong (机车电传动)
The slewing bearing is the key part of articulated bogie. In order to realize the function of connecting, carrying and turning, three-ring structure slewing bearing was designed. The slewing bearing structure was analyzed, the load safety factor of the slewing bearing was calculated. The design rationality was verified by bearing checking and partial load experiment, which showed that the slewing bearing could meet the working requirements.